Electrodeposition of lead‐free solder alloys - Goh, Y.; Haseeb, A.S. Md. Abdul; Sabri, M.F.M. (Emerald, 2013)
Purpose – The purpose of this paper is to enhance the understanding on the electrodeposition of various lead (Pb)‐free solder alloys, so that new studies can be carried out to solve processing issues.